Coagulation factor Xa promotes metastasis through endothelial cell activation - Arce Arata, Maximiliano Amadeo. (2019)
Tesis (Doctor in Biological Sciences with a mention in Physiological Sciences)--Pontificia Universidad Católica de Chile, 2019